The dual role of tumor lymphatic vessels in dissemination of metastases and immune response development. (2nd July 2016) - Stachura, Joanna; Wachowska, Malgorzata; Kilarski, Witold W.; Güç, Esra; Golab, Jakub; Muchowicz, Angelika
ABSTRACT: Lymphatic vasculature plays a crucial role in the immune response, enabling transport of dendritic cells (DCs) and antigens (Ags) into the lymph nodes. Unfortunately, the lymphatic system has also a negative role in the progression of cancer diseases, by facilitating the metastatic spread of many carcinomas to the draining lymph nodes. The lymphatics can promote antitumor immune response as well as tumor tolerance. Here, we review the role of lymphatic endothelial cells (LECs) in tumor progression and immunity and mechanism of action in the newest anti-lymphatic therapies, including photodynamic therapy (PDT).